Water-dispersible Ti3C2Tz MXene nanosheets by molten salt etching - Kailash Arole (Elsevier, 2021)
Summary: Molten-salt etching of Ti3AlC2 MAX phase offers a promising route to produce 2D Ti3C2Tz (MXene) nanosheets without hazardous HF. However, molten-salt etching results in MXene clays that are not water dispersible, thus preventing further processing. This occurs because molten-salt etching results in a lack of -OH terminal groups rendering the MXene clay hydrophobic. Here, we demonstrate a method that produces water-dispersible Ti3C2Tz nanosheets using molten salt (SnF2) to etch. In molten salt etching, SnF2 diffuses between the layers to form AlF3 and Sn as byproducts, separating the layers. The stable, aqueous Ti3C2Tz dispersion yields a ζ potential of −31.7 mV, because of -OH terminal groups introduced by KOH washing. X-ray diffraction and electron microscopy confirm the formation of Ti3C2Tz etched clay with substantial d-spacing as compared with clay etched with HF. This work is the first to use molten salt etching to successfully prepare colloidally stable aqueous dispersions of Ti3C2Tz nanosheets.